Analysis on water replenishment effect of ecological sluices in the middle reaches of the Tarim River - Feng, Siyang; Xu, Yi; Shi, Rui; Huang, Xiaorong; Wu, Yongxiang; Wang, Gaoxu (Frontiers in Environmental Science, 2025)
To evaluate the water replenishment effect of ecological sluices in the Tarim River’s mainstream and the water demand for ecological restoration, this study focused on the area controlled by a typical sluice group in the middle reaches. Using Landsat imagery (2000–2020) and the Penman-Monteith method, we quantified the spatiotemporal evolution of vegetation water consumption and ecological water demand, proposing corresponding sluice operation strategies. The results show: (1) From 2000 to 2020, natural vegetation consumed 1.62 × 108 m3 of water on average, increasing by 0.1 × 108 m3 per 5 years. Woodland and grassland expanded by 67.18 km2 per 5 years, demonstrating effective ecological restoration. (2) Vegetation water consumption varied spatiotemporally, peaking near sluice-fed branch canals and declining with distance from the river. The highest consumption occurred in 2015, concentrated in mid-growth periods. (3) Ecological water demands were: 1.76 × 108 m3 (maintaining 2020 conditions), 1.62 × 108 m3 (2000–2020 average), and 2.01 × 108 m3 (optimal 2015 level). By linking sluice impacts to vegetation water use and quantifying restoration needs, this study provides a scientific basis for water management and ecological regulation.